Primary ovarian leiomyoma associated with endometriotic cyst presenting with symptoms of acute appendicitis: a case report - Puljiz Zvonimir; Tučkar Neven; Leniček Tanja; Tomas Davor; Ledinsky Mario; Krušlin Božo (BMC, 2009)
Abstract Background Ovarian leiomyoma is a rare benign tumor that accounts for 0.5 to 1% of all benign ovarian tumors. It probably arises from smooth muscle cells in the ovarian hilar blood vessels but there are other possible origins including cells in the ovarian ligament, smooth muscle cells or multipotential cells in the ovarian stroma, undifferentiated germ cells, or cortical smooth muscle metaplasia. Additionally, smooth muscle metaplasia of endometriotic stroma, smooth muscle present in mature cystic teratomas, and smooth muscle in the walls of mucinous cystic tumor may explain their occurrence in the ovary in some cases. Case presentation A 31-year-old woman was admitted to our surgical emergency service with a one-day history of appendicitis-like symptoms. Upon laparotomy, there was a solid, oval left-sided ovarian tumor located behind the uterus. The tumor was sent to the pathology department. A diagnosis of primary ovarian leiomyoma associated with an endometriotic cyst was established. Conclusion The origin of ovarian leiomyoma is still unresolved. In our case, the tumor probably arose from smooth muscle cells derived from myofibroblasts that originate from metaplastic ovarian stromal cells present in the rim of the endometriotic cyst. Despite its rarity, ovarian leiomyoma should be considered in the differential diagnosis of ovarian spindle cell tumors. Appropriate diagnosis may require additional immunohistochemical analysis in some cases.